Color Modulation in Morpho Butterfly Wings Using Liquid Crystalline Elastomers. (14th June 2020) - De Bellis, Isabella; Ni, Bin; Martella, Daniele; Parmeggiani, Camilla; Keller, Patrick; Wiersma, Diederik S.; Li, Min-Hui; Nocentini, Sara
Abstract : Nature provides well‐engineered and evolutionary optimized examples of brilliant structural colors in animals and plants. Morpho butterflies are among the well‐known species possessing iridescent bright blue coloration due to multiple optical effects generated by the complex structuration of the wing scales. Such surprising solution can be replicated to fabricate efficient devices. Maybe even more interesting, novel approaches can be developed to combine wings with synthetic smart materials to achieve complex structures responsive to external stimuli. This study demonstrates the proof of concept of an innovative biotic–abiotic hybrid smart structure made by the integration of a butterfly wing with thermoresponsive liquid crystalline elastomers, and their capability to actuate the mechanical action of the wing, thus controlling its spectral response. Exploiting two fabrication strategies, it is demonstrated how different mechanisms of color tuning can be achieved by temperature control. In addition, due to the thermally induced mechanical deformation of the elastomer and superhydrophobic properties of the wing, a potential self‐cleaning behavior of the bilayer material is demonstrated. Abstract : A biotic–abiotic system made by Morpho butterfly and liquid crystalline elastomers (LCEs) enables the structural color tuning together with self‐cleaning capability. Exploiting the LCE thermosensitive behavior, the color tuning is achieved by two integration strategies: a macroscopic deformation induces an iridescence variation, whereas a nanoscale contraction generates a color shift through the lamellae interspacing variation.